Rendahnya Posisi Tawar Nelayan Eretan Kulon Di Dunia Maritim - Setyadarma, David Michael; Vincent Pratama Duslam; Duslam, Vincent Pratama (Universitas Katolik Parahyangan, 2023)
This research utilizes qualitative and descriptive research methods to explore strategies that can enhance the well-being of fishermen in Eretan Kulon Village. The study reveals several challenges that need to be addressed, including low bargaining power in the maritime industry, low levels of formal education, unsupportive thinking paradigms, FOMO phenomenon, dependence on the sea, service deficiencies, and malpractices at the Fish Auction Place. To overcome these challenges, strategic measures are required, such as improving formal education and relevant training, diversifying livelihoods, and strengthening the Village Cooperative Unit (KUD) Mina Bahari and other economic organizations through enhanced services, supportive programs, and strict supervision. This research provides an in-depth understanding of the challenges faced by fishermen in Eretan Kulon Village and offers concrete recommendations for the government, economic organizations, and local community to formulate strategic actions aimed at enhancing the well-being of fishermen and the community in Eretan Kulon Village